Commercial gaming devices for stroke upper limb rehabilitation: The stroke survivor experience. (May 2020) - Thomson, Katie; Pollock, Alex; Bugge, Carol; Brady, Marian C
Introduction: Approximately 30% of stroke survivors experience an upper limb impairment, which impacts on participation and quality of life. Gaming devices (Nintendo Wii) are being incorporated into rehabilitation to improve function. We explored the stroke survivor experience of gaming as an upper limb intervention. Methods: Semi-structured, individual interviews with stroke survivors living within the UK were completed. Interviews were audio-recorded, transcribed verbatim and analysed using Framework methods. Transcripts were coded and summarised into thematic charts. Thematic charts were refined during analysis until the final framework emerged. Results: We captured experiences of 12 stroke survivors who used Nintendo Wii. Gaming devices were found to be acceptable for all ages but varying levels of enthusiasm existed. Enthusiastic players described gaming as having a positive impact on their motivation to engage in rehabilitation. For some, this became a leisure activity, encouraging self-practice. Non-enthusiastic players preferred sports to gaming. Conclusion: An in-depth account of stroke survivor experiences of gaming within upper limb rehabilitation has been captured. Suitability of gaming should be assessed individually and stroke survivor abilities and preference for interventions should be taken into consideration. There was no indication that older stroke survivors or those with no previous experience of gaming were less likely to enjoy the activity.